2015
DOI: 10.2214/ajr.14.12939
|View full text |Cite
|
Sign up to set email alerts
|

Extracapsular Extension in Prostate Cancer: Added Value of Diffusion-Weighted MRI in Patients With Equivocal Findings on T2-Weighted Imaging

Abstract: OBJECTIVE. The objective of our study was to evaluate diffusion-weighted imaging (DWI) and T2-weighted imaging for predicting extracapsular extension (ECE) in patients with prostate cancer. MATERIALS AND METHODS. One hundred seventeen patients underwent preoperative 3-T MRI and radical prostatectomy. Two radiologists evaluated ECE with T2-weighted imaging based on the Prostate Imaging Reporting and Data System (PI-RADS). Then, the apparent diffusion coefficient (ADC) of the tumor calculated from two b values (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 31 publications
4
52
1
Order By: Relevance
“…a At mpMRI (multiparametric magnetic resonance imaging). This result is in line to previous studies [10][11][12][18][19][20], suggesting that this nomogram could be of help to confirm results from standard T2-WI, which is currently recognized as the most accurate sequence to detect macroscopic ECE.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…a At mpMRI (multiparametric magnetic resonance imaging). This result is in line to previous studies [10][11][12][18][19][20], suggesting that this nomogram could be of help to confirm results from standard T2-WI, which is currently recognized as the most accurate sequence to detect macroscopic ECE.…”
Section: Discussionsupporting
confidence: 91%
“…Although T2-WI has some limitations (long acquisition times and susceptibility to motion artefacts), with the possibility of an impaired image quality, ADC from DWI is associated with high sensitivity to detect ECE [10][11][12][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the low spatial resolution of DWI, studies have shown its potential role in predicting ECE. 17,18 The study of Woo et al 18 concluded that T2WI and DWI were independently associated with ECE and ADC had an incremental value in patients without a high suspicion of ECE on T2WI. The role of DWI in seminal vesicle invasion has also been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…We acquired multiplanar (axial, coronal, and sagittal) T2-weighted images with the following parameters: repetition time range/echo time range, 3,400–4,500/100–140; slice thickness, 3 mm; interslice gap, 0.3 mm; matrix, 512×318; field of view, 22 cm; number of signals acquired, 2; and parallel imaging acceleration factor, 2. We performed axial fat-suppressed single-shot echoplanar diffusion-weighted imaging with the following parameters: repetition time range/echo time, 6,500/77; slice thickness, 3.5 mm; no interslice gap; matrix, 192×192; field of view, 30 cm; number of signals acquired, 6; parallel imaging acceleration factor, 2; and b-values, 0 and 1,000 s/mm 2 [14]. Because our hospital only had MRI equipment capable of producing images with b-values ≤1,000 s/mm 2 between 2007 and 2013, we were unable to use b-values >1,400 as recommended by the new Prostate Imaging Reporting and Data System guidelines (ver.…”
Section: Methodsmentioning
confidence: 99%